(3NdGUI SjQ SjO GdHTQs - (3eMH GdOjf GdWHQj , CMeO Hf YHO Gddg Hf eMeO TjN GdMQe, eMH GdOjf CHh GdYHGS,J (B694 (3g` s ((3eMH Hf eMeO Hf efUhQ GdMSjfi GdMdHi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi fhGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B58 - (3U(B94s
(3YdjgG NW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B159 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B298s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B361 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B125 s
Keywords: (3GdJGQjNs